2011
DOI: 10.1590/s0066-782x2011001200012
|View full text |Cite
|
Sign up to set email alerts
|

Intervenções nutricionais em Síndrome Metabólica: uma revisão sistemática

Abstract: There is no consensus on the most appropriate nutritional strategy for treating metabolic syndrome (MS), such that cardiovascular risk is reduced. This study was designed to assess the strength of evidence of the benefits of various nutritional interventions in MS remission. Performed in Medline, Cochrane Library and PubMed databases, the virtual search consisted of randomized clinical trials published between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…Dietary patterns such as the Mediterranean diet have been shown to decrease the risk and progression of MetS (Esposito et al, 2013). At a basic level, diets low in saturated fats, and rich in fiber, monounsaturated oils, vitamins and minerals have been found to be protective against MetS (de Leão et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns such as the Mediterranean diet have been shown to decrease the risk and progression of MetS (Esposito et al, 2013). At a basic level, diets low in saturated fats, and rich in fiber, monounsaturated oils, vitamins and minerals have been found to be protective against MetS (de Leão et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies conducted among people with schizophrenia reported higher intake of salt, total sugars, and fats, primarily saturated fatty acids (SFA), along with the lower intake of dietary fiber and fruits when compared to the general population [12][13][14][15]. Even though such dietary habits are generally associated with unfavorable health implications [16][17][18][19], there is still no consensus on the most effective nutrition therapy for the MetS [20]. Therefore, it is of an utmost importance to develop an adequate nutritional intervention program that would be effective in its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence suggests that dietary factors are the cornerstone for the prevention and treatment of MS [14]–[16]. Furthermore, with respect to dietary factors studies, researchers have usually focused predominantly on the effects of individual nutrients and sometimes foods, but rarely on dietary patterns.…”
Section: Introductionmentioning
confidence: 99%